The Political Economy of Copyright - Haggart, Blayne (Copyfight, 2014)
Although it has only recently emerged into the mainstream of political debate, copyright has long been a controversial subject. The law tends to depoliticize issues so that they seem technical and settled, even as they remain contested.² However, underneath the seemingly solid surface of settled law lies an ongoing battle among various business and social groups to expand copyright in some cases and in the service of some interests, and to restrict it in others. In this battle, the United States and its content industries are the primary actors behind the global expansion of copyright since the mid-1980s, as well